First Records of Meiobenthic Etinosomatids (Crustacea: Copepoda: Harpacticoida) from Sarawak Coastal Waters, Borneo, Malaysia - Fatimah Atirah, Mohamad; Shabdin, Mohd Long; Awangku Shahrir Naqiuddin, Awg Suhaili (Sarawak Museum Department, 2020)
The present study was the first taxonomy work conducted to record meiobenthic Etinosomatids along Sarawak coastal waters. The coastline of Sarawak stretched about 1035 km long and contains an extensive continental shelf area, areas of high biological productivity and a high marine coastal biodiversity. This survey yielded several specimens of ectinosomatid harpacticoid copepods. The specimens represent 3 unrecorded species (Halophytophilus fusiformis, Glabrotelson psammae and Arenosetella kaiseri) in Sarawak waters. These species were described, illustrated and compared with their original descriptions. Some recorded species were showed minor remarks which differed slightly from the original description. Setal formulae and detailed descriptions of all species obtained are given to aid identification for references in future.